2007
DOI: 10.1093/eurheartj/ehl490
|View full text |Cite
|
Sign up to set email alerts
|

Targeted stent use in clinical practice based on evidence from the BAsel Stent Cost Effectiveness Trial (BASKET)

Abstract: Patients with angioplasty of small vessels or bypass grafts seem to benefit from DES use, in long-term outcome, in contrast to patients with large native vessel stenting where there might even be late harm. Still, this hypothesis needs to be tested prospectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…In a previous analysis of the same dataset, both SVG and vessel size were identified as predictors of late outcome [29]. The present study serves as an exploratory analysis of this finding investigating baseline and outcome differences between SVG and similarly sized native vessels treated with different stent types including all patients with a PCI using a stent ≥3 mm in diameter; however, it was allowed to post-dilate 3.5-mm stents up to 4.0 mm, if necessary.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous analysis of the same dataset, both SVG and vessel size were identified as predictors of late outcome [29]. The present study serves as an exploratory analysis of this finding investigating baseline and outcome differences between SVG and similarly sized native vessels treated with different stent types including all patients with a PCI using a stent ≥3 mm in diameter; however, it was allowed to post-dilate 3.5-mm stents up to 4.0 mm, if necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the RRISC (Reduction of Restenosis in Saphenous Vein Grafts with Cypher Sirolimus-Eluting Stents) study demonstrated conflicting results with DES reducing late loss after 6 months [26] but exposing to a long-term hazard with increased all-cause mortality after 3 years [27]. In contrast, a previous exploratory analysis of BASKET (Basel Stent Kosten Effektivitäts Trial/Basel Stent Cost Effectiveness Trial) [28] demonstrated that SVG lesions carried a high risk of recurrent clinical events which could be reduced by the use of DES, but specific results were lacking [29]. …”
Section: Introductionmentioning
confidence: 99%
“…79 Similarly, a stratified subgroup analysis of a trial suggested a benefit of DES in terms of cardiac death, MI, and repeat revascularization in small vessels (stent diameter Ͻ3.0 mm) but the potential of harm in larger vessels. 80 Accordingly, BMS remain a valuable alternative to DES in large vessels with discrete lesions. A step further, balloon angioplasty remains a valid option in selected patients.…”
Section: Patient and Lesion Selectionmentioning
confidence: 99%
“…[18][19][20][21][22] Moreover, patients with small vessels or bypass grafts seem to benefit from the use of DES, as far as long-term outcome is concerned, in contrast to patients with large native vessel stenting in whom there can be late harm. 23,24 Emerging evidence of stent thrombosis that is fatal is a major limitation to the use of DES and so far there is consensus for the discontinuation of clopidogrel, because although the benefit of DES in reducing TLR is maintained, there is an increase in late cardiac death or nonfatal MI, possibly related to late stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%